Anti-inflammatory compounds and a new sesquiterpene lactone from Centaurea gabrieljanae Greuter - ŞEN, ALİ; BİTİŞ, LEYLA (My University, 2024)
The traditional use of Centaurea spp. for anti-inflammatory purposes is widespread among the people in Turkiye. For this, the methanol extract of Centaurea gabrieljanae and sub-fractions of the methanol extract were tested for anti-inflammatory activity using 5-LOX, while their antioxidant activities, total phenol, and total flavonoid contents were also examined. The ethyl acetate fraction exhibited potent anti-inflammatory activity (IC50 = 3.864 ± 0.9 µg/ml), from which five known compounds (astragalin, picein, p-hydroxy benzoic acid, 3,4-dimethoxy-cinnamic acid, 4-hydroxybenzoic acid 4-O-β-glucopyranoside) and a new sesquiterpene lactone named Pterochlorin were obtained. Pterochlorin showed potent anti-inflammatory activity with a value of IC50 12.71 ± 0.7 µg/ml compared to standard indomethacin. Similarly, astragalin was found to be strong (IC50 = 18.23 µg/ml). In addition, 4-hydroxybenzoic acid 4-O-β-glucopyranoside was isolated for the first time in Centaurea species, and its anti-inflammatory activity was tested. This study may be a guide for the discovery of a new anti-inflammatory drug derived from natural sources.
Keywords: Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; Tarım ve Çevre Bilimleri (AGE); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Bitki ve Hayvan Bilimleri; BİTKİ BİLİMLERİ; KİMYA, ANALİTİK; KİMYA, ORGANİK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Agriculture & Environment Sciences (AGE); Natural Sciences (SCI); Life Sciences (LIFE); PLANT & ANIMAL SCIENCE; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; PLANT SCIENCES; CHEMISTRY, ANALYTICAL; CHEMISTRY, ORGANIC; BIOCHEMISTRY & MOLECULAR BIOLOGY; Fizik Bilimleri; Bitki Bilimi; Organik Kimya; Physical Sciences; Plant Science; Organic Chemistry; anti-inflammatory; Centaurea gabrieljanae; flavonoid; sesquiterpene lactone